Are there co-occurrence patterns that structure snake communities in Central Brazil? - Franca, FGR; Araujo, AFB (Brazilian journal of biology, 2007)
The main factors that structure Neotropical animal communities have been the subject of discussion in ecology communities. We used a set of null models to investigate the existence of structure in snake communities from the Cerrado in Central Brazil in relation to the co-occurrence of species and guilds concerning specific resources. We used fragments (conservation units) inside the Distrito Federal and neighbor municipalities. In spite of recent human colonization in the region from the end of the 1950’s, intense habitat modification and fragmentation has taken place. Sixty three snake species are present in the Distrito Federal. Co-occurrence analysis of species and guilds associated to snake diets and habitats suggested a lack of organization. The homogeneity of habitats in Central Brazil and the minor importance of ecological effects can lead to random arrangement. Os processos que levam à estruturação de comunidades animais neotropicais têm sido sujeito de ampla discussão em ecologia de comunidades. Usou-se um conjunto de modelos nulos para investigar a existência de estrutura em comunidades de serpentes presentes no Cerrado do Brasil Central, em relação à coocorrência de espécies e de guildas relacionadas a recursos específicos. As localidades utilizadas para as análises representam fragmentos de habitats dentro do Distrito Federal e em municípios vizinhos. Apesar da recente colonização humana da região, datada para o final da década de 50, a intensidade da modificação e fragmentação dos habitats no Brasil Central têm sido enorme. Sessenta e três espécies de serpentes estão presentes no Distrito Federal. As análises dos padrões de coocorrência tanto para as espécies quanto para guildas relativas à dieta e ao uso do ambiente sugeriram ausência de organização. A homogeneidade dos ambientes no Brasil Central e a baixa importância de efeitos ecológicos podem levar ao arranjo randômico.